Gray wolves - Herrington, Lisa M. (2019)
Did you know that gray wolves are highly social animals with a complex method of communicating-or that they often mate for life? Learn fascinating facts like these-and more-all in the pages of this book! This title offers a complete picture of the animal- from birth to adulthood- and describes its place in our world, including how humans impact it and its environment.
Wolves in the wild -- Live in a pack -- Bringing up pups -- Blast to the past -- The struggle for survival.
Includes bibliographical references (page 46) and index.
8-11
Keywords: Gray wolf -- Juvenile literature; Wolves -- Juvenile literature